Return mobility of scientists and knowledge circulation: an exploratory approach to scientists attitudes and perspectives - Fontes, Margarida (2012)
This paper addresses the mobility of scientists and its implications for countries with weaker scientific and technological systems. It focuses on the “return dilemma” and, using the Portuguese case as empirical setting, discusses the conditions for return, the diaspora option and the role of policies in minimising the impacts of unbalanced flows. We propose a method to identify and locate key expatriate scientists (a basic problem in mobility research) and conduct an exploratory application of that methodology in a specific field, in order to collect some information on scientists’ trajectories as well as gaining some preliminary insights on their attitudes towards the home country.